Sutureless intrascleral intraocular lens fixation with lamellar dissection of scleral tunnel - Kawaji T (Dove Medical Press, 2016)
Takahiro Kawaji,1,2 Tomoki Sato,2 Hidenobu Tanihara11Department of Ophthalmology, Faculty of Life Sciences, Kumamoto University, Chuo-ku, 2Sato Eye & Internal Medicine Clinic, Kumamoto, JapanPurpose: To report the results of sutureless scleral fixation of a posterior chamber intraocular lens (IOL) by using our developed simple technique.Methods: We retrospectively reviewed the medical records of 48 eyes of 47 patients who underwent sutureless intrascleral IOL fixation by using our modified technique. A 25-gauge microvitreoretinal knife was used to perform sclerotomies and create limbus-parallel scleral tunnels with lamellar dissection in which the haptics were fixed.Results: The IOLs were fixed and centered well. The mean follow-up period was 26.7 months. Postoperative complications included smooth vitreous hemorrhage in four eyes (8.3%), cystoid macular edema in two eyes (4.2%), and iris capture of the IOL in two eyes (4.2%). No other complications, such as breakage of the IOL, spontaneous IOL dislocation, or retinal detachment, were detected during the follow-up period.Conclusion: The lamellar dissection of the limbus-parallel scleral tunnel can simplify the forceps-assisted introduction of the haptics into the scleral tunnel, and this technique seemed to be safe.Keywords: intraocular lenses, ophthalmologic surgical procedures, intrascleral fixation, sutureless fixation